2021
DOI: 10.5194/hess-25-4631-2021
|View full text |Cite
|
Sign up to set email alerts
|

Bright and blind spots of water research in Latin America and the Caribbean

Abstract: Abstract. Water resources management in Latin America and the Caribbean is particularly threatened by climatic, economic, and political pressures. To assess the region's ability to manage water resources, we conducted an unprecedented literature review of over 20 000 multilingual research articles using machine learning and an understanding of the socio-hydrologic landscape. Results reveal that the region's vulnerability to water-related stresses, and drivers such as climate change, is compounded by research b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The water scarcity analysis we conduct in this study is rooted in an explicit characterization of global multisector dynamic interactions across systems and scales (Reed et al., 2022), including within LAC. Most research on the future of water in Latin America has not taken a multisector, multi‐scale approach (DeVincentis et al., 2021), though previous studies have demonstrated the importance of this style of analysis (Santos Da Silva et al., 2019; Wild, Khan, Zhao, et al., 2021), particularly given the strong linkages between the region's water and land systems. For example, Flachsbarth et al.…”
Section: Introductionmentioning
confidence: 99%
“…The water scarcity analysis we conduct in this study is rooted in an explicit characterization of global multisector dynamic interactions across systems and scales (Reed et al., 2022), including within LAC. Most research on the future of water in Latin America has not taken a multisector, multi‐scale approach (DeVincentis et al., 2021), though previous studies have demonstrated the importance of this style of analysis (Santos Da Silva et al., 2019; Wild, Khan, Zhao, et al., 2021), particularly given the strong linkages between the region's water and land systems. For example, Flachsbarth et al.…”
Section: Introductionmentioning
confidence: 99%